Lanthanide luminescence sensing of copper and mercury ions using an iminodiacetate based Tb(III)-cyclen chemosensor - GUNNLAUGSSON, THORFINNUR; MCMAHON, BRIAN (My University, 2010)
The design, synthesis and photophysical evaluation of 1.Tb.Na, a Tb(III)-cyclen based sensor, possessing a phenyl iminodiacetate based receptor, for the selective detection of Cu(II) and Hg(II) ions in water is demonstrated. Sensitisation of the Tb(III) 5D4 excited state was achieved by excitation of the phenyl receptor, which in water gave rise to characteristic time-delayed and line-like Tb(III) emission. The Tb(III) emission was shown to be pH independent over the physiological pH window. The changes in the Tb(III) emission were monitored by carrying out metal titrations using various group I, II and transition metal ions. Of these, only the titrations of Cu(II) and Hg(II) gave rise to modulations in the Tb(III) emission; resulting in quenching in the Tb(III) emission by ca. 65% and 40%, respectively.
PUBLISHED
Keywords: Biochemistry; Nanoscience & Materials